KEMAMPUAN MENGANALISIS KESALAHAN BERBAHASA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS ISLAM RIAU - Alber, Alber; Hermaliza, Hermaliza (Jurnal Sastra Indonesia, 2020)
Learning outcomes of language error analysis courses are students mastering linguistic theories, types of language analysis, and language error analysis techniques and are able to apply theories of language error analysis at each level of linguistics. But unfortunately, the learning achievement is difficult to achieve because based on the phenomenon that the writer found as lecturer in the course of language error analysis, many students could not reach the determined target and did not have the criteria set by the lecturer or university lecturer. Based on this problem, the formulation of the problem of this research is how to analyze the errors of grammar study program of Indonesian Language and Literature in Riau Islamic University. The study used a descriptive method with a research population of all sixth semester students of the Indonesian Language and Literature Education Study Program at the Riau Islamic University and used random sampling as a research sample. Research Results The ability to analyze language errors in the level of phonology of Indonesian Language and Literature Education Study Program at Islamic University with an average score of 47.32 with a very poor category. Meanwhile, the ability to analyze language errors at the level of morphology of Indonesian Language and Literature Education Study Program Students at Islamic University with an average score of 33.13 with the category of failure.